Functional Outcome of Percutaneous Ilio-sacral Screw Fixation for Posterior Pelvic Ring Injuries - Pandey, Nitesh Raj; Khakurel, Paras; Aryal, Rajendra; Bhusal, Rajan; Banskota, Bibek (Nepal Orthopaedic Association Journal, 2025)
BACKGROUND This study aimed to assess the functional outcomes of percutaneous ilio-sacral screw fixation in the treatment of posterior pelvic ring injuries.METHODS A total of 34 (out of 42) adult patients treated with percutaneous ilio-sacral screw fixation for posterior pelvic ring injuries, with or without associated anterior ring injuries between January 2020 and December 2023, were included in this study. There were 35% females and 65% males, all of whom completed follow-up evaluation. Clinical and radiological follow-up assessments were performed at six months, and functional outcomes were evaluated using the Majeed Functional Score.RESULTS The mean age of patients was 34.29 years ±13.29. The average hospital length of stay was 22.88 days ±18.63. Patients were categorized by Tile classification, with B3 injuries being the most common (26.47%), followed by C2 injuries (20.59%). Injury mechanisms included two-wheeler accidents (35.29%), pedestrian accidents (17.65%), and falls from height (14.71%). Functional outcomes assessed using the Majeed Functional Score showed excellent results in 79.41% of patients, good in 8.82%, fair in 8.82%, and poor in 2.94%. There was no incidence of neurological injury in this cohort.CONCLUSION The findings suggest that, if executed correctly, percutaneous ilio-sacral screw fixation is a safe and effective method for managing posterior pelvic ring injuries. Most patients achieved excellent functional outcomes, aligning with previous research on this treatment modality.